2000
DOI: 10.1038/35036614
|View full text |Cite
|
Sign up to set email alerts
|

Role for the p53 homologue p73 in E2F-1-induced apoptosis

Abstract: The transcription factor E2F-1 induces both cell-cycle progression and, in certain settings, apoptosis. E2F-1 uses both p53-dependent and p53-independent pathways to kill cells. The p53-dependent pathway involves the induction by E2F-1 of the human tumour-suppressor protein p14ARF, which neutralizes HDM2 (human homologue of MDM2) and thereby stabilizes the p53 protein. Here we show that E2F-1 induces the transcription of the p53 homologue p73. Disruption of p73 function inhibited E2F-1-induced apoptosis in p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
485
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 659 publications
(510 citation statements)
references
References 28 publications
19
485
2
1
Order By: Relevance
“…E2F1 has been previously shown by us and others to activate p73 transcription by binding to E2F binding sites in the TAp73 promoter (Irwin et al, 2000;Stiewe and Pu¨tzer, 2000). In contrast, the DNp73 promoter is not activated by E2F1 Waltermann et al, 2003).…”
Section: Repression Of Telomerase Activity By P73mentioning
confidence: 75%
“…E2F1 has been previously shown by us and others to activate p73 transcription by binding to E2F binding sites in the TAp73 promoter (Irwin et al, 2000;Stiewe and Pu¨tzer, 2000). In contrast, the DNp73 promoter is not activated by E2F1 Waltermann et al, 2003).…”
Section: Repression Of Telomerase Activity By P73mentioning
confidence: 75%
“…Several reports have shown that DNA damage results in E2F1-mediated transcription of p73a, a p53 homolog involved in the activation of p53-responsive target genes and apoptosis (Irwin et al, 2000). As shown in Figure 6c, the sequential treatment of Cis-Nut induced a timedependent increase in p73a, whereas the treatment with Cis alone induced a slight increase above baseline.…”
Section: Nutlin-3a Induces Apoptosis In P53wt Cells and Enhances Chemmentioning
confidence: 77%
“…However, E2F1À/À knockout mice develop a broad spectrum of tumors, suggesting that E2F1 also functions as a tumor suppressor. Indeed, several authors reported that E2F1 can induce apoptosis through p53-dependent (Kowalik et al, 1995;Qin et al, 1994;Wu and Levine, 1994) and p53-independent mechanisms (Irwin et al, 2000), by upregulating apoptotic genes like Apaf-1 (Furukawa et al, 2002), p73 (Stiewe and Putzer, 2000), caspase 3 and 7 (Muller et al, 2001), Noxa and PUMA (Hershko and Ginsberg, 2004). Furthermore, forced expression of E2F1 caused increased sensitivity to DNA-damaging agents and topoisomerase II inhibition in a p53-independent manner (Nip et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…McKeon and coworkers [48] showed that p73 is not required for AICD induced by secondary TCR stimulation of CD4 + T cells, recovered from a Rag2 -/-reconstitution system, which argues against the general concept that p73 is essential for T cell AICD [25,36]. This suggests that p73 plays an important role in the apoptosis of the primary T cell response, but is less important for secondary responses.…”
Section: Discussionmentioning
confidence: 99%
“…p73 isoforms resulting from the usage of an alternative promoter located in the third intron lack the transactivation domain and act as dominant-negative forms (DNp73) that have antiapoptotic function [35]. The major form expressed in activated T cells is p73a [25,36].In order to investigate the mechanism of increased CD8 + T cell proliferation in SAP -/-mice, we utilized OVA-specific OT-I TCR-transgenic mice. This allowed us to further examine the activation, proliferation and apoptosis of antigen-specific CD8 + T cells on both WT and SAP -/-background.…”
mentioning
confidence: 99%